2018
DOI: 10.17010/ijom/2018/v48/i5/123445
|View full text |Cite
|
Sign up to set email alerts
|

Buying Behaviour of Herbal Cosmetics by Women Consumers : An Exploratory Study in Kolkata

Abstract: Executive SummarySince the concept of environmental consciousness has become a necessity to save the mankind, promoting consumption of green products is the need of hour, owing to the fact that green products are environment friendly or sustainable products and are organic in nature. It is evident that the feeling for the health of environment and consumers is being resulted in the emergence of the usage of green products at the cost of traditional or conventional products. However, the magnitude of usage of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Consumer perception and buying behaviour towards ayurvedic medicines across India was studied by several researchers in India and there is consensus among the researchers that (a) people are more interested in buying Ayurvedic products compared to the chemical product/medicine (Sharma & Khanna, 2017) and (b) that customers prefer to buy ayurvedic products for relief from stressful working culture, exhaustive lifestyle, the endless quest for peace and growing ailments issues with less healthy environment (Sangeetha, 2017). Some studies performed in other countries (e.g., Thailand, Bangladesh) also emphasised that (a) customers have high trust in herbal products, (b) consumers were influenced by the physical appearance of the herbal products, attractive texture, odour, penetration-characteristic, viscosity, cash discount, gift premium, fortune, tarot horoscope, make-up and massage workshop and (c) women show growing importance to herbal cosmetic products (Chattaraj et al, 2018; Thanisorn et al, 2017). In one study conducted in Siberia, majority of Siberians are well-educated and they consume herbal remedies on their own initiative and manufacturers of herbal drugs in Siberia also educate potential consumers on reliable use of herbal medicines and herbal dietary supplements in order to improve their awareness on extensive use of herbal remedies by overcoming safety and potential risks while using combination with other drugs (Samollk et al, 2013).…”
Section: Ayurveda and Nature-based Herbal Productsmentioning
confidence: 99%
“…Consumer perception and buying behaviour towards ayurvedic medicines across India was studied by several researchers in India and there is consensus among the researchers that (a) people are more interested in buying Ayurvedic products compared to the chemical product/medicine (Sharma & Khanna, 2017) and (b) that customers prefer to buy ayurvedic products for relief from stressful working culture, exhaustive lifestyle, the endless quest for peace and growing ailments issues with less healthy environment (Sangeetha, 2017). Some studies performed in other countries (e.g., Thailand, Bangladesh) also emphasised that (a) customers have high trust in herbal products, (b) consumers were influenced by the physical appearance of the herbal products, attractive texture, odour, penetration-characteristic, viscosity, cash discount, gift premium, fortune, tarot horoscope, make-up and massage workshop and (c) women show growing importance to herbal cosmetic products (Chattaraj et al, 2018; Thanisorn et al, 2017). In one study conducted in Siberia, majority of Siberians are well-educated and they consume herbal remedies on their own initiative and manufacturers of herbal drugs in Siberia also educate potential consumers on reliable use of herbal medicines and herbal dietary supplements in order to improve their awareness on extensive use of herbal remedies by overcoming safety and potential risks while using combination with other drugs (Samollk et al, 2013).…”
Section: Ayurveda and Nature-based Herbal Productsmentioning
confidence: 99%
“…In an article regarding the Buying Behavior of Herbal Cosmetics by Women Consumers Chattaraj et al [13] investigated the significance of association between the demographic and socioeconomic attributes and frequency of buying herbal cosmetics. The findings of the study showed a significant relationship between age, household income, and education with frequency of purchasing herbal cosmetics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Indian herbal products industry is booming annually; thus the competition between established players is also accelerating. Recognising the fundamental interactions between the numerous demographic and socioeconomic variables of end users is crucial for sustaining and performing in the competitive industry (Chattaraj, Mazumder and Lahiri 2018). The 'SHIFT' hypothesis implied that buyers are more likely to participate in environmentally sustainable activities whenever the message or meaning takes care of the following psychological factors: social impact, habit development, individual self, emotions and cognition, and tangibility (White, Habib and Hardi 2019).…”
Section: Literature Reviewmentioning
confidence: 99%